Making rights claims : a practice of democratic citizenship - Zivi, Karen (New York : Oxford University Press, 2012)
'Making Rights Claims' argues that understanding and assessing the relationship between rights and democracy requires a new approach to the study of rights. Zivi combines insights from speech act theory with recent developments in democratic and feminist thought to develop a theory of the performativity of rights claiming.
Includes bibliographical references and index.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Keywords: Human rights; Civil rights